2020
DOI: 10.1097/meg.0000000000002011
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary biliary cholangitis: results from a large real-life observational study in France and Belgium

Abstract: Background and aims: To assess the characteristics, care, treatment response, and outcomes of primary biliary cholangitis (PBC) patients recently followed-up by hepato-gastroenterologists in various French and Belgian healthcare settings. Methods: This retrospective cohort study included patients with PBC who recently visited 79 hepato-gastroenterologists in France and Belgium. Data were collected at the time of diagnosis and at last visit and were compared according to biochemical response (BR) to ursodeoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another large study, this time across France and Belgium, investigated data from two time points, the date of diagnosis and last visit, of 436 patients with PBC followed by hepatologists with good experience with PBC [9 ▪ ]. This study showed that the evaluation of the disease stage was quite often incomplete (in 25% of patients, neither liver biopsy nor LSM was assessed at baseline) and nonresponsiveness to ursodeoxycholic acid (UDCA) according to Paris criteria frequently went unrecognized by clinicians who therefore overestimated disease control.…”
Section: Large Study Supports Vibration-controlled Transient Elastogr...mentioning
confidence: 99%
“…Another large study, this time across France and Belgium, investigated data from two time points, the date of diagnosis and last visit, of 436 patients with PBC followed by hepatologists with good experience with PBC [9 ▪ ]. This study showed that the evaluation of the disease stage was quite often incomplete (in 25% of patients, neither liver biopsy nor LSM was assessed at baseline) and nonresponsiveness to ursodeoxycholic acid (UDCA) according to Paris criteria frequently went unrecognized by clinicians who therefore overestimated disease control.…”
Section: Large Study Supports Vibration-controlled Transient Elastogr...mentioning
confidence: 99%
“…Primary biliary cholangitis (PBC) is a chronic cholestatic immune liver disease characterized by persistent cholestasis, interlobular bile duct damage, liver fibrosis, eventual cirrhosis, and death [ 1 ]. Its prevalence in Europe has an overall rate of 22.27 cases per 100,000 inhabitants and a pooled incidence rate of 1.7 new cases per 100,000 inhabitants per year, with a female predominance (1.6–4.8:1 female: male ratio) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of PBC are cholestasis caused by abnormal bile acids (BAs) metabolism and interlobular bile duct damage caused by abnormal immune response [ 1 ]. Studies had suggested the critical role of microbiome by interacting with BAs metabolism and immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Primary biliary cirrhosis (PBC) is clinically a type of autoimmune cholestatic liver disease characterized by serum autoantibody antimitochondrial antibodies (AMAs) ( 1 , 2 ), chronic progressive cholestasis, interlobular bile duct damage, liver inflammation, eventual cirrhosis, and death ( 3 , 4 ). Studies have found that the incidence and prevalence of PBC have increased globally in the past few decades ( 5 , 6 ), especially among women ( 7 ).…”
Section: Introductionmentioning
confidence: 99%